Scientific activity of Ya.K. Syrkin at the Faculty of Chemistry of the IvanovoVoznesensk Polytechnic Institute and in the Ivanovo Institute of Chemistry and Technology (1918–1932) - A. S. Malyasova; O. I. Koifman (Тонкие химические технологии)
Objectives. Preserving the continuity of scientific schools and increasing scientific motivation is critical for educating new generations of researchers. One way to solve this problem is to promote the historically significant achievements of outstanding scientists working in the field, without which the foundations of modern chemical technologies cannot be imagined. The field of physical chemistry benefited immensely from the contributions made by Professor Yakov Kivovich Syrkin. This article is devoted to the analysis of the growth of Ya.K. Syrkin as a scientist and discusses his main scientific contributions to physical and quantum chemistry. Methods. The article was prepared using archival materials, bibliographic references, original texts of articles, and scientific reports. Results. The article details and documents the main scientific achievements of Ya.K. Syrkin during his work at the Ivanovo-Voznesensk Polytechnic Institute and the Ivanovo Institute of Chemistry and Technology between 1918 and 1932, showing his growth and development as a young scientist through his interactions with teachers and colleagues. Syrkin’s research on chemical equilibrium, reaction kinetics, thermodynamics, catalysis, solution theory, solvate effects, and colloidal systems are presented herein. Conclusions. A retrospective analysis of the career of Ya.K. Syrkin shows the scope of his research interests and his ability to build on the foundations provided by great predecessors such as Gibbs, Van’t Hoff, Arrhenius, Ostwald, and Nernst. A comprehensive study of fundamental and applied aspects of physical chemistry guided Syrkin’s approach to understanding the importance of molecular structure and the nature of chemical bonds in all observed chemical phenomena.